2019
DOI: 10.1002/adts.201900079
|View full text |Cite
|
Sign up to set email alerts
|

Optimized‐Surface Wettability: A New Experimental 3D Modeling Approach Predicting Favorable Biomaterial–Cell Interactions

Abstract: Despite several decades of research on biomedical implant materials, the identification of predictive and robust in vitro characteristics of cell support ability and viabilities—as indicators of biocompatibility and future implant‐tissue integration—remain elusive. This study addresses the phenomenology of cell–implant interfaces based on experimental, theoretical, and numerical analysis of cell response to functionalized bioceramic coatings of commercial titanium implants, cp‐Ti. A variable spectrum of coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…While a cell would have achieved a passive interfacial free energy minimization state by simply remaining in the specific geometry, such a change may be necessary, for instance, in order to satisfy the thermodynamic function boundary condition. This requirement corroborates that cell viability is more likely to occur only at this specific interfacial energy window of opportunity because biological factors may be implicated in this process, for instance, opposing internal stresses due to nuclear and cytoplasmic resistance, which may limit the maximum and minimum values of γ c and γ i . Herein, we state that membrane tension changes during stretching, thereby satisfying the boundary conditions.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…While a cell would have achieved a passive interfacial free energy minimization state by simply remaining in the specific geometry, such a change may be necessary, for instance, in order to satisfy the thermodynamic function boundary condition. This requirement corroborates that cell viability is more likely to occur only at this specific interfacial energy window of opportunity because biological factors may be implicated in this process, for instance, opposing internal stresses due to nuclear and cytoplasmic resistance, which may limit the maximum and minimum values of γ c and γ i . Herein, we state that membrane tension changes during stretching, thereby satisfying the boundary conditions.…”
Section: Resultssupporting
confidence: 73%
“…From a static point of view (cells on the surface in an equilibrium state), the interfacial energy γ i could assume values ranging from 30 to 0 mN m –1 , which exhibits an opportunity window for cells in viable states. In our previous work, we identified values of γ i ∼5 mN m –1 with high viability for fibroblast cells . By analogy, the optimized steady-state γ c is found to be 51 mN m –1 right after the cell spreading-attachment stage on the surface.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The motivation for using gold is two-fold. First, studies correlating surface wettability and cell adhesion have reported a water contact angle of 65 ± 5° as the “magic number” for ideal cell adhesion on biomaterials. , This value corresponds to the water contact angle of clean gold. Second, gold is biocompatible and used for implants and prosthetic implant components, such as screws .…”
Section: Materials and Methodsmentioning
confidence: 99%